INCREASING CREATIVITY AND LEARNING OUTCOME HISTORY OF INDONESIA ISLAMIC MATERIALS INTO THE KING'S PALACE THROUGH A SCIENTIFIC APPROACH IN PROBLEM-BASED LEARNING FOR STUDENTS OF CLASS X AP 3 SMK NEGERI 1 PURWODADI - Saswito Hadi Prayitno (Yayasan Citra Dharma Cindekia, 2022)
This study aims to improve creativity and learning outcomes of Indonesian history of Islamic material entering the king's palace through a scientific approach in problem-based learning for students of class X AP 3 SMKN 1 Purwodadi in semester 2 of 2014/2015. The subjects of this study were 39 students. The research method used is Classroom Action Research which is carried out in 2 cycles. Primary data in the form of learning outcomes pre-cycle, cycle 1, and cycle 2. Secondary data obtained from colleagues/ collaborators in the form of observations about creativity both cycle 1 and cycle 2. Data collection techniques using documentation, observation/observations, and written tests. Observation is carried out directly to observe and dig up information about the condition of the learning process. This study uses comparative descriptive data analysis. The implication of this research is that the scientific approach in problem-based learning can increase the creativity of learning Indonesian History empirically, the results of pre-cycle and cycle 1 show that the results of creativity in learning Indonesian History increase both theoretically and empirically. Scientific approach with problem-based learning can improve creativity and learning outcomes of Indonesian History. The results of pre-cycle and cycle 1 showed that the results of learning Indonesian history increased both theoretically and empirically, from an average of 55 to an average of 64. The results of cycle 1 and cycle 2 showed that the results increased both theoretically and empirically, namely increasing creativity and learning outcomes with a cycle average 1 obtained 65 to cycle 2 obtained an average of 69.